PENEGAKAN HUKUM ADMINISTRASI TERHADAP KEGIATAN YANG TIDAK BERDAMPAK PENTING YANG BELUM MEMILIKI DOKUMEN UKL-UPL (Studi PT. Hadi Putra Makmur Kota Semarang) - Istiqomah Istiqomah (Jurnal Ilmiah Dinamika Hukum, 2019)
ABSTRACT An environmental permit is a permit given to any person or initiator who wishes to undertake a business and / or activity that is required to be UKL-UPL in the framework of environmental protection and management as a condition of obtaining a business and / or activity license. Violations committed by PT. Hadi Putra Makmur related to the issue of obligations and prohibitions, especially regarding licensing, efforts to manage and monitor the environment, hereby the supervision of DLH enforces by giving administrative sanctions. The above is the basis for the author to take the title "ADMINISTRATIVE LAW ENFORCEMENT ON IMPORTANT ACTIVITIES THAT DO NOT HAVE DOCUMENTS UKL-UPL (Study of PT. Hadi Putra Makmur Semarang City)." In this research, the authors raise the problems, namely: a. How is administrative law enforcement for activities that have no significant impact that do not yet have UKL-UPL documents? b. What are the obstacles that arise in the administration of administrative law for activities that do not have significant impacts that do not have UKL-UPL documents? c. What is the Role of Administrative Law in Enforcement of Environmental Law? The method used is to use the type of juridical normative research with descriptive analytical research specifications, secondary data sources with data collection methods through literature study and interviews, and the method of presentation and data analysis methods using descriptive analytical methods. The purpose of this study is to explain the application of administrative sanctions for activities that do not have significant impacts that do not have UKL-UPL documents. Barriers that arise in the enforcement of administrative sanctions for activities that do not have a significant impact that do not have UKL-UPL documents, and the role of administrative law in environmental law enforcement. The results showed that PT. Hadi Putra Makmur has violated licensing, environmental management and monitoring efforts, DLH Semarang city has imposed administrative sanctions in the form of government coercion in accordance with PP no. 37 of 2012 concerning environmental permits. Administrative sanctions are legal instruments used for the first time by DLH in enforcing cases conducted by PT. Hadi Putra Makmur. Keywords: Administrative Enforcement, Environmental Permit, UKL-UPL